Performance Management and Operational Efficiency in Universities in Kenya: A Moderating Effect of Corporate Culture - Ng’ang’a, Monica; K’Obonyo, Peter; Muindi, Florence; Kariuki, Margaret (Journal of Business and Social Sciences Research, 2025)
Performance management evolves within organisations, appearing as either formal systems or informal daily practices. Kenyan universities, pivotal to national development, confront shrinking budgets, rising competition, and demanding stakeholders, making efficient operations imperative. This study investigated whether corporate culture moderates the link between performance management and operational efficiency. Institutional theory framed the analysis, while Schein’s layered view of culture explained cultural influences. Performance management behaviours were measured with a structured questionnaire; corporate culture was captured with the Organisational Culture Assessment Instrument. A positivist, cross-sectional census surveyed registrars in all 72 Kenyan universities; 80 % responded. Composite indices for performance management and culture were created, and Data Envelopment Analysis estimated operational efficiency from longitudinal secondary data. Diagnostic tests satisfied regression assumptions. Simple regression showed performance management positively correlated with efficiency (r = 0.571). Stepwise regression confirmed a significant moderating effect of culture. Mission and clan cultures dominated, entrepreneurial traits remained weak, and several universities displayed low efficiency. Findings enrich higher-education management literature in Africa. The study recommends cultural shifts towards entrepreneurship, institutional specialisation, and stronger efficiency orientation.